Gut microbiome in non-alcoholic fatty liver disease - Anastasios Mpountouridis; Christina Tsigalou; Ioanna Bezirtzoglou; Eugenia Bezirtzoglou; Elisavet Stavropoulou (Frontiers in Gastroenterology)
Non-alcoholic fatty liver disease (NAFLD) has a rapidly growing incidence worldwide, affecting approximately one-third of world population. The disturbance of gut commensal bacteria impacting host’s homeostasis is referred to as gut dysbiosis. The gut microbiome contributes to the pathogenesis of NAFLD through various pathways. Gut microbiota is at constant interactions with the intestinal epithelial barrier and affects its integrity. Through gut-liver axis, gut microbiota may influence liver immune function. The release of lipopolysaccharides (LPS) from intestines to portal vein which are transported to the liver, may trigger hepatic inflammation, steatosis and even fibrosis. Moreover, the gut microbiome induces the conversion of primary bile acids (BAs) to secondary BAs, which activates intestinal receptors, such as FXR and TGR5. FXR activation decreases fat absorption and thus reduces hepatic lipid accumulation, while TGR5 activation promotes the release of glucagon-like peptide-1 (GLP-1) in blood. Furthermore, gut ethanol-producing bacteria has been implicated in NAFLD development. Additionally, in NAFLD there is a reduction in intestinal levels of short-chain fatty acids, such as butyrate, propionate and acetate. Many bacterial alterations have been observed in NAFLD, including the increased Bacteroidetes and decreased Firmicutes. Many probiotics have been tried in NAFLD prevention and management, including a plethora of strains from Lactobacilli, Bifidobacteria and Streptococcus and some of them have promising perspectives. There is also some promising data from the administration of prebiotics (such as inulin and fructo-oligosaccharides) and symbiotics (probiotics plus prebiotics). Faecal microbiota transplantation (FMT) is yet to be evaluated for its efficacy against NAFLD.